(untitled) (Journal of Oriental Studies, 2018)
The paper is devoted to analyze the origin of tribes who created Avar khanate on base of anthropology researching. The history of Avar Khanate in Middle ages in assosiation of Turkic tribes living in considerable territory of Eurasian continent. In this case Avar history studying by Europe and СIS scientists and has been presented different arguements. Of course, today, in time of developing science and and technique we find the lost, it is time to honor our fogotten history. The one of secrets which leaves without appropriate attention is analyzing and arguing the origin of Avars on base of athropological researching through writing sources and remains. About Avar ethnogenesis history exist some valueable sources of Middle age chroniclers in Latin. Among them in 5th century Priisk Paninski, historians of Byzantine Empire Theophylact Simokatta, Menander Protector, Syrian John Atascii, in chronicles of Fredegar, Georgian chronicler Kartlis Tskhovreba, Goth Jordanian, Russian chroniclers, the Arab travellers as Ibn Khordadbekh etc. sources the problem of ethnogenesis of Avars was considered. Also in the East Europe, especially Szentendre, Boccia, Kunszentmiklós – Babon settlements belong to Avars.